2019
DOI: 10.1016/j.mjafi.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Measles, mumps, and rubella: A cross-sectional study of susceptibility to vaccine-preventable diseases among young people in India

Abstract: Background: Global elimination of vaccine preventable diseases, such as measles, mumps and rubella is a priority. Many countries have reported diminishing of antibody titres against these diseases among young population as immunization coverage of adolescents and adults in not monitored. The objective of this study was to determine the susceptibility against measles, mumps and rubella among young adults. Methods:In this cross-sectional study serological evidence of susceptibility to measles, mumps and rubella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Although the measles, mumps and rubella vaccine has been administered more commonly in recent years in India, it is still not included in the routine vaccination program. 26 When evaluating anti-rubella Total cost (TRY † ) 400 563.28 †TRY: New Turkish Lira. ; ‡SOGC: The Society of Obstetricians and Gynaecologists of Canada.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the measles, mumps and rubella vaccine has been administered more commonly in recent years in India, it is still not included in the routine vaccination program. 26 When evaluating anti-rubella Total cost (TRY † ) 400 563.28 †TRY: New Turkish Lira. ; ‡SOGC: The Society of Obstetricians and Gynaecologists of Canada.…”
Section: Discussionmentioning
confidence: 99%
“…We considered the rubella immunization programs of various countries, accessibility of healthcare services and hygienic conditions to be the most important factors for this low anti‐rubella IgM positivity rate. Although the measles, mumps and rubella vaccine has been administered more commonly in recent years in India, it is still not included in the routine vaccination program . When evaluating anti‐rubella IgG results, however, the seroprevalence positivity rate was found to be 95.27% (9293/9754).…”
Section: Discussionmentioning
confidence: 99%
“…Migrant workers who participated in the survey on latent tuberculosis and provided consent for their data and residual sera to be used for future research were eligible for inclusion in our study. For this serological study, the minimum sample size for each country of origin and birth cohort was determined based on published reports of measles seroprevalence in Bangladesh [ 13 ], China [ 14 ], India [ 15 ] and Malaysia [ 16 ] (Additional file 1 : Table S1) with a confidence level of 95% and relative precision of 5%. For migrant workers from Indonesia, Myanmar and the Philippines, we assumed their measles antibody prevalence was at least 85% in each birth cohort, which gave a minimum sample size of 272 with a confidence level of 95% and relative precision of 5%.…”
Section: Methodsmentioning
confidence: 99%
“…10 In recent years, many measles outbreaks have been reported among adolescents and adults. [11][12][13] A review article from the Indian subcontinent revealed the changing trend in the endemicity of hepatitis A infection, with more susceptible adolescents/ adults than previously observed. Older age groups were reported to present with more severe symptoms of hepatitis A.…”
mentioning
confidence: 99%